Pengaruh Disiplin Kerja dan Efikasi Diri terhadap Kinerja Pegawai Melalui Motivasi Kerja sebagai Variabel Intervening (Studi Empirik pada Balai Pelatihan Lingkungan Hidup dan Kehutanan Bogor) - Zulfiqar, Mohammad Alif; Entang, Muhamad; Tukiran, Martinus (Ekonomis: Journal of Economics and Business, 2024)
This research analyzes the relationship between work discipline, self-efficacy, work motivation and employee performance. The research method used quantitative instruments and survey methodology. The population of this study consisted of 110 BPLHK Bogor employees. Descriptive inferential statistical research and path analysis are implemented in the sampling method. Data analysis consists of descriptive statistics and structural equation modeling (SEM). The results of this research prove that there is a direct influence between work discipline, self-efficacy and work motivation on employee performance. Furthermore, there is a direct influence between work discipline and self-efficacy on work motivation. This research also found that work motivation variables can intervene in work discipline and self-efficacy variables on the performance of BPLHK Bogor employees.